APOLLONIUS AND THE END OF THE AENEID*. (20th November 2014) - Kelly, Adrian
<x content-type="archive" xml:space="preserve">Abstract</x> The death of Turnus is one of the Aeneid's most controversial and variously interpreted episodes – anything from the triumphant vindication of Aeneas and the Roman future, to the poet's last, resounding plaint against Augustan totalitarianism, with all the more nuanced shades of opinion in between. Virgilian scholarship has recently become tired of the opposition between 'optimist' and 'pessimist' perspectives, but one piece of potentially important evidence has not found its way into the argument. As often, it is a matter of intertexts, and it begins, unsurprisingly, with the Iliad.